Rhetorical Moves, Intensification, and Mitigation in Motivation Letters for Acceptance into Graduate Schools in México - Urizar Ocampo, Carolina; Velásquez Upegui, Eva Patricia (Íkala, Revista de Lenguaje y Cultura, 2023)
The motivation letter is a promotional genre often requested for acceptance into post-graduate programs in Mexico. Even though universities and research centers provide some guidelines for its preparation, there is not a clear description of this genre's textual structure or of its pragmatic features. Given this situation, we developed a qualitative research study which aimed to describe the rhetorical movements and the use of intensification and attenuation mechanisms deployed by applicants to two post-graduate programs of two universities in Mexico in 30 motivation letters written in Spanish language. For the analysis, we used the ATLAS.ti 9 software. Findings show that four rhetorical movements characterize this genre, namely, (a) to explicitly state the reasons for applying, (b) to present the applicant's objectives, (c) to persuade the reader, and (d), to express future expectations. Meanwhile, intensification appears to be more common than attenuation, suggesting that the applicants strive to build a valuable self-image for the selection committee while keeping some degree of modesty, given the asymmetry in the reviewer-applicant relationship. This study highlights the importance of integrating this genre and its discursive features in the teaching of academic writing at universities, acknowledging the discursive characteristics of each disciplinary community.